Законодавча та нормативна база регулювання документно-інформаційних комунікацій підприємства - Химиця, Наталія; Мельник, Дарина (Видавництво Львівської політехніки, 2017)
This article describes a system of legislative and regulatory document information communications company. Тhe main blocks of laws governing document-information communications company the defined. The hierarchy of regulations in the document-information communications now offered.
Keywords: інформація; документи; комунікації; документно-інформаційні комунікації; закони; нормативні акти; підприємство; управління